1987
DOI: 10.1111/j.1398-9995.1987.tb00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐like anticoagulants in asthma

Abstract: In a previous study, and in the present study, we have found that the baseline plasma samples of patients with asthma contain average levels of an endogenous heparin-like material (EHM) that is significantly higher than that noted in non-allergic, non-asthmatic controls. This material appears to have properties of both heparin and heparan sulfate. Three out of six patients responding to inhalational antigen challenge displayed an acute increment in EHM concentration that coincided with a fall in FEV values. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Heparin-like material was demonstrated in the blood of patients with peripheral arterial occlusive disease, all of whom showed an increased coagulation tendency compared with healthy controls, in a manner that correlated with disease severity (Shankar et al, 2008). By contrast, patients with allergic disease have an increased level of circulating "heparin-like material" and these patients have been suggested to have less calcification of the major arteries, suggestive of a role for endogenous heparin in preventing cardiovascular problems (Lasser et al, 1987). Human mast cells have been reported to release heparin after allergen stimulation (Green et al, 1993).…”
Section: F Endogenous Heparinmentioning
confidence: 96%
See 1 more Smart Citation
“…Heparin-like material was demonstrated in the blood of patients with peripheral arterial occlusive disease, all of whom showed an increased coagulation tendency compared with healthy controls, in a manner that correlated with disease severity (Shankar et al, 2008). By contrast, patients with allergic disease have an increased level of circulating "heparin-like material" and these patients have been suggested to have less calcification of the major arteries, suggestive of a role for endogenous heparin in preventing cardiovascular problems (Lasser et al, 1987). Human mast cells have been reported to release heparin after allergen stimulation (Green et al, 1993).…”
Section: F Endogenous Heparinmentioning
confidence: 96%
“…Many proteins display basic amino acid residues on their surfaces, sometimes clustered into patches of positive charge that form socalled heparin binding domains. Because heparin itself is located in mast cell granules, liberated into the surrounding tissue only briefly on degranulation (Green et al, 1993;Wang and Kovanen, 1999), it is likely to come into contact with only the subset of proteins found in mast cell granules, the immediate ECM and possibly the circulation, as elevated levels of heparin-like material have been measured in patients with allergic diseases who undergo regular mast cell degranulation (Lasser et al, 1987). Interestingly, such patients also have a mild hemostatic defect consistent with elevated heparin levels in the circulation (Szczeklik et al, 1991).…”
Section: B Heparin Interactions With Proteinsmentioning
confidence: 99%
“…More importantly, we have demonstrated that this process proceeds more rapidly in atopic or asthmatic individuals than in individuals without these abnormalities [1]. Asthmatics can be demonstrated to have higher concentrations than do nonasthmatics of heparin/heparan sulfate when these molecules are isolated from their neutralizing substances [2, 3] (Figure 3). …”
Section: Activation Of the Contact System And Negative Surfacesmentioning
confidence: 99%
“…In addition, an increased level of an endogenous 'heparin-like material' has been reported in the plasma of allergic subjects (Lasser et al, 1987). Heparin has been shown to inhibit activation of the complement system (Kazatchkine et al, 1981;Ekre et al, 1986), neutrophil chemotaxis (Matzner et al, 1984) and eosinophil infiltration (Hanss et al, 1989;Seeds & Page, 1992).…”
Section: Introductionmentioning
confidence: 99%